Factors affecting technical change of productivity growth in rainbow trout aquaculture in Iran - Hassanpour, Behrooz; Ismail, Mohd Mansor; Mohamed, Zainal Abidin; Kamarulzaman, Nitty Hirawaty (Academic Journals, 2011)
Rainbow trout farming is an important contributor to the aquaculture industry in Iran. This study number of the factors including the socio-economic factor was considered for analysing the factors affecting technical change in trout aquaculture. A two-stage estimation procedure for this analysis was applied. The Malmquist index is then employed to measure the productivity and technical change in the first stage, while the pooled logit and tobit models were performed in the second stage so as to ascertain factors affecting the technical change or innovation improvement. The study was conducted to utilize panel data of 207 trout farms in the country over a five-year period from 2003 to 2007. The results of this study revealed that the total factor productivity (TFP) growth of rainbow trout farming in the aquaculture sector is substantially formed from technical efficiency change rather than technical change or innovation improvement. Hence, Iran still has a room to improve the TFP growth in the trout aquaculture, and this can be done by shifting its production frontier through improving innovation and development of new technologies. Based on the marginal effects analysis derived from the pooled logit/tobit regression, the factors that mostly affected technical change positively were suitability of water temperature (13 to 18°C), extension workshop and educational level of the manager. Conversely, the negative factors included the governmental insurance coverage, pond size and being government tenure, such as public companies and cooperatives.